A Screen for Epigenetically Silenced microRNA Genes in Gastrointestinal Stromal Tumors. - Mai Isosaka; Takeshi Niinuma; Masanori Nojima; Masahiro Kai; Eiichiro Yamamoto; Reo Maruyama; Takayuki Nobuoka; Toshirou Nishida; Tatsuo Kanda; Takahiro Taguchi; Tadashi Hasegawa; Takashi Tokino; et al. (PLoS ONE, 2015)
Dysregulation of microRNA (miRNA) has been implicated in gastrointestinal stromal tumors (GISTs) but the mechanism is not fully understood. In this study, we aimed to explore the involvement of epigenetic alteration of miRNA genes in GISTs.GIST-T1 cells were treated with 5-aza-2'-deoxycytidine (5-aza-dC) and 4-phenylbutyric acid (PBA), after which miRNA expression profiles were analyzed using TaqMan miRNA arrays. DNA methylation was then analyzed using bisulfite pyrosequencing. The functions of miRNAs were examined using MTT assays, wound-healing assays, Boyden chamber assays and Matrigel invasion assays. Gene expression microarrays were analyzed to assess effect of ectopic miRNA expression in GIST-T1 cells.Of the 754 miRNAs analyzed, 61 were significantly upregulated in GIST-T1 cells treated with 5-aza-dC plus PBA. Among those, 21 miRNA genes were associated with an upstream CpG island (CGI), and the CGIs of miR-34a and miR-335 were frequently methylated in GIST-T1 cells and primary GIST specimens. Transfection of miR-34a or miR-335 mimic molecules into GIST-T1 cells suppressed cell proliferation, and miR-34a also inhibited migration and invasion by GIST-T1 cells. Moreover, miR-34a downregulated a number of predicted target genes, including PDGFRA. RNA interference-mediated knockdown of PDGFRA in GIST-T1 cells suppressed cell proliferation, suggesting the tumor suppressive effect of miR-34a is mediated, at least in part, through targeting PDGFRA.Our results suggest that miR-34a and miR-335 are candidate tumor suppressive miRNAs in GISTs, and that they are frequent targets of epigenetic silencing in GISTs.